Blood–brain barrier permeability of normal‐appearing white matter in patients with vestibular schwannoma: A new hybrid approach for analysis of T1‐W DCE‐MRI. Issue 1 (24th January 2017) - Li, Ka‐Loh; Zhu, Xiaoping; Zhao, Sha; Jackson, Alan
Abstract : Purpose: To develop and assess a "hybrid" method that combines a first‐pass analytical approach and the Patlak plot (PP) to improve assessment of low blood–brain barrier permeability from dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) data. Materials and Methods: Seven patients with vestibular schwannoma were enrolled. T 1 ‐W DCE imaging was acquired on a 1.5T scanner. Normal‐appearing white matter (NAWM) was divided into four regions of interest (ROIs) based on the magnitude of changes in longitudinal relaxation rate (ΔR1) after gadolinium administration. Kinetic analysis of ROI‐averaged contrast agent concentration curves was performed using both the conventional PP and the hybrid method. Computer simulated uptake curves that resemble those from NAWM were analyzed with both methods. Percent deviations (PD) of the "measured" values from the "true" values were calculated to evaluate accuracy and precision of the two methods. Results: The simulation showed that, at a noise level of 4% (a noise level similar to the in vivo data) and using a signal intensity (SI) averaging scheme, the new hybrid method achieved a PD of 0.9 ± 2.7% for v p, and a PD of –5.4 ± 5.9% for K trans . In comparison, the PP method obtained a PD of 3.6 ± 11.3% for v p, and –8.3 ± 12.8% for K trans . One‐way analyses of variance (ANOVAs) showed significant variations from the four WM regions ( P < 10 −15 for ΔR1; P < 10 −6 for K trans ; P < 10 −4 for v p ). Conclusion: Both computer simulation and in vivo studies demonstrate improved reliability in v p and K trans estimates with the hybrid method. Level of Evidence: 3 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:79–93